"Everyday I am Çapuling": Keeping Dirlik's theoretical history in focus. Issue 4 (2nd October 2021) - Prazniak, Roxann
ABSTRACT: Four years after his death and in a world significantly transformed by recent events, Arif Dirlik's final thoughts carry a heightened urgency for discussions of critical theory and the actions they might inspire. Considering the panoply of topics that concerned his acute intellect, Arif identified two issues he deemed most important for the present state of humanity: an historical understanding of the construct of "China" and the legacy of the French Enlightenment. Other problems, as he saw it, depended on getting these two multifaceted and far-reaching cases of contested history right. Critical analysis employed in this exploration would by extension connect with and continue to animate current debates on race, environment, and democracy. In a concluding thought experiment intended to spin his theoretical history approach into future scholarship and activism, Dirlik explored the complexities of class and racism in a series of incidents from late Qing dynasty/US relations.